The Future of Butyric Acid in Industry. (19th April 2012) - Dwidar, Mohammed; Park, Jae-Yeon; Mitchell, Robert J.; Sang, Byoung-In
Abstract : In this paper, the different applications of butyric acid and its current and future production status are highlighted, with a particular emphasis on the biofuels industry. As such, this paper discusses different issues regarding butyric acid fermentations and provides suggestions for future improvements and their approaches.